Analisis kontribusi motivasi dan disiplin kerja terhadap kinerja karyawan KSPPS Abdi Kerta Raharja, Tangerang - Adham, Ibnu (Universitas Tangerang Raya, 2024)
This research aims to determine the influence of work ethic and motivation partially and simultaneously on the performance of KSPPS Abdi Kerta Raharja workers. Data is handled via SPSSv.26. The results of surveys and interviews were used in the quantitative methodology of this research. A random sample of the total population yielded 50 responses. The methodology used includes coefficient of determination testing, hypothesis testing, classical assumption testing, multiple linear regression testing, and validity testing. The research results show that to a limited extent the work discipline variable (X1) has an influence on the employee performance variable (Y), with a calculated t value of 12.274 which is greater than t table 1.920 and a sig of 0.020 which is lower than = 0.05. The employee performance variable (Y) is significantly influenced by the motivation variable (X2), where the calculated t value of 13.680 is higher than the t table of 1.920 and the sig is 0.000 lower than = 0.05. The employee performance variable (Y) is significantly influenced by the remuneration variable (X3) with a sig value of 0.000 which is smaller than = 0.05. From the results of the ANOVA or Fcount test, it can be seen that the work discipline (X1) and motivation (X2) variables have a significant influence on employee performance (Y), with an Fcount value of 198.229 which is greater than 3.19 and a significance level of 0.000